Stylistic Patterns and Cultural Identity in Contemporary Indonesian Poetry: A Linguistic Approach - Deo Renaldi Saputra; Ainur Rofiq Sofa (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study investigates the interplay of stylistic patterns, code-switching, and metaphorical pragmatics in shaping cultural identity in contemporary Indonesian poetry, adopting a qualitative empirical approach through the analysis of twenty poems published between 2020 and 2025. Utilizing purposive sampling, the corpus encompasses works from both emerging and established poets, reflecting diverse regional, social, and generational perspectives. Data collection combined textual compilation with contextual metadata, while analysis employed a coding schema integrating stylistic, morphological, and pragmatic features, validated through expert review and inter-coder reliability. Findings reveal that code-switching and code-mixing are strategically deployed to negotiate hybrid identities, signaling local heritage, cosmopolitan sensibilities, and generational positioning, whereas metaphorical devices serve pragmatic functions that embed ethical, social, and historical meanings. Morphological innovations and phonostylistic features enhance semantic density and aesthetic impact, highlighting the deliberate orchestration of linguistic resources. The study demonstrates that contemporary Indonesian poetry functions as a semiotically rich site for cultural expression, providing theoretical and methodological insights into the analysis of hybrid linguistic strategies and the dynamic construction of cultural identity in literary texts.